DO THE PRICE AND TASTE MATTER TO COFFEE DRINKERS? - Ratna Mutia; Khairul Aswadi; Martahadi Mardhani; Nasir Nasir; Rizka Rizka; Zulfikar Zulfikar (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2022)
This article explores several characteristics, such as price and taste, to influence the behavior of coffee drinkers in Banda Aceh City, Indonesia. Using standard multiple regression analysis, it turns out that coffee taste affects coffee drinkers' behavior. On the other hand, the price of coffee drinks does not affect the behavior of coffee drinkers. This study shows that the taste of coffee is more important for coffee customers to decide to drink coffee. Further research is suggested by increasing the number of samples and expanding the study area. An in-depth discussion is highly recommended for debate and practical and theoretical consequences for further study.